A long chain alcohol as support in solid phase organic synthesis - Yeni Nurlela,; Adrian J. Minnaard,; Sadijah Achmad,; Deana Wahyuningrum, (Universiti Kebangsaan Malaysia, 2011)
The solid phase synthesis is a method by which organic compound synthesis are performed on a support. With this method, the purification can be carried out easily by simple filtration and washing procedures. Long-chain alcohol (C-100 alcohol) can be used as a support because of its insolubility in organic solvents and its simple structure which enables it to be stable in various reaction conditions. In this study, a 4-aminopyridine derivative has been synthesized from C-100 β-keto ester and a cyano enamine using tin(VI)chloride as catalyst. C-100 β-keto ester was obtained by transesterification of long chain alcohol (the support) with ethyl acetoacetate using boric acid protocol. The cyano enamine was successfully synthesized by Thorpe-Ziegler cyclization initiated by sodium hydride. The 4-aminopyridine derivative was successfully cleaved from the support using sodium isopropoxide in refluxing isopropanol. From the 1H-NMR spectrum at ~ 120oC, it was found that the cleaved support has the same spectrum with the long-chain alcohol used in the beginning of reaction, thus, this long chain alcohol can be reused for other reactions